2017
DOI: 10.3390/ijms18050969
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hydroquinone Mediated Cytotoxicity and Hypopigmentation Effects from UVB-Irradiated Arbutin and DeoxyArbutin

Abstract: Arbutin (Arb) and deoxyArbutin (dA) are both effective hypopigmentation agents. However, they are glucoside derivatives of hydroquinone (HQ), which may be decayed into HQ under higher energy environments. Therefore, safety and toxicity are very important issues when considering the usage of these compounds. However, no study has verified the properties of Ultra-Violet B (UVB)-irradiated Arb and dA. In this work, we investigated the cytotoxicity and hypopigmentation effects of UVB-irradiated Arb and dA in Detro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…The cells were sub-cultured in T75 flasks three to four days each to sustain regular growth. 29 Melan-a (Mel-a) cells were purchased from Welcome Trust Functional Genomic Cell Bank, St. George Medical School, University of London, London (United Kingdom). Cells were grown in RPMI-1640 media supplemented with 10% FBS, 1% P/S Solution, 100x, 1% amphotericin B, 2 mM L-glutamine, and 200nM tetradecanoyl phorbol acetate (TPA).…”
Section: Cell Culturementioning
confidence: 99%
“…The cells were sub-cultured in T75 flasks three to four days each to sustain regular growth. 29 Melan-a (Mel-a) cells were purchased from Welcome Trust Functional Genomic Cell Bank, St. George Medical School, University of London, London (United Kingdom). Cells were grown in RPMI-1640 media supplemented with 10% FBS, 1% P/S Solution, 100x, 1% amphotericin B, 2 mM L-glutamine, and 200nM tetradecanoyl phorbol acetate (TPA).…”
Section: Cell Culturementioning
confidence: 99%
“…Hydroquinone, another phenol‐based compound, is considered as the gold‐standard treatment for melasma. Melanocyte cytotoxicity related to hydroquinone is a recognized phenomenon and is thought to be due to generation of reactive oxygen species, which in turn initiate an autoimmune response, potentially giving explanation to depigmentation at distant sites 5,6 . The genetic predisposition to such autoimmunity is offered as an explanation into why this phenomenon may not be seen in all individuals exposed to these chemicals 5 .…”
Section: Topical Agent Typical Percentage Preparations Uses Recommended Regimenmentioning
confidence: 99%
“…There are other phenolic cosmetic skin‐lightening agents, including arbutin, resorcinol, kojic acid and salicylic acid, but melanocyte cytotoxicity has not been reported with these ingredients. However, an in vitro study reported cell cytotoxicity with ultraviolet (UV)B‐irradiated arbutin and deoxyarbutin, which correlated with the UVB‐induced degradation into hydroquinone 6 …”
Section: Topical Agent Typical Percentage Preparations Uses Recommended Regimenmentioning
confidence: 99%
“…However, there are still the presence of side effects and limitations in these compounds, such as allergic reactions, irritation, cellular damage, and carcinogenesis. [9][10][11] Resveratrol is a stilbenoid compound present in the polyphenol group. It has been discovered as a good depigmentation agent that can inhibit tyrosinase activity and reduce melanin production.…”
Section: Introductionmentioning
confidence: 99%